Effects of substituting soybean meal with fermented rapeseed meal mixture on the growth performance, slaughter performance, meat quality, blood biochemical indices and intestinal barrier function in Langshan Chickens - Zhaochen Wang; Tong Xing; Lin Zhang; Liang Zhao; Feng Gao (Poultry Science, 2024)
This study aimed to explore the effects of substituting soybean meal with a mixture of solid-state fermented rapeseed meal, apple pomace, and wheat bran on the growth performance, slaughter performance, meat quality, blood biochemical indices and intestinal barrier function of Langshan chickens. A total of 144 30-day-old Langshan chickens with similar body weights were randomly divided into three treatment groups, with six replicates per group and eight chickens per replicate: the control group (CON) was fed a corn-soybean meal basal diet, while the rapeseed meal mixture group (RSM) and the fermented rapeseed meal mixture group (FRSM) were fed diets substituting 5 % of soybean meal with rapeseed meal mixture and fermented rapeseed meal mixture, respectively. The trial lasted from 30 to 58 days of age. The results showed that compared to the CON group, the RSM group exhibited no significant changes in average daily feed intake (ADFI), average daily gain (ADG) and feed to gain ratio (F/G) (P > 0.05); the dressing percentage, half-eviscerated yield and eviscerated yield decreased (P < 0.05); the pH24h and yellowness of breast muscle increased (P < 0.05); the crypt depth of the jejunum decreased, and the villus height/crypt depth ratio increased (P < 0.05); the serum D-lactic acid content decreased (P < 0.05). Compared to the CON group, the FRSM group exhibited no significant changes in ADFI, ADG and F/G (P > 0.05); the eviscerated yield increased (P < 0.05); the serum glucose and uric acid levels decreased (P < 0.05); the crypt depth of the jejunum decreased, and the villus height/crypt depth ratio increased (P < 0.05); the serum D-lactic acid content decreased (P < 0.05). Furthermore, compared to the RSM group, the FRSM group exhibited no significant changes in ADFI, ADG and F/G (P > 0.05); the dressing percentage, half-eviscerated yield and eviscerated yield increased (P < 0.05); the pH24h of breast muscle decreased; the serum glucose and uric acid levels decreased (P < 0.05).In conclusion, RSM reduced the slaughter performance of Langshan chickens, while FRSM improved their slaughter performance. Both RSM and FRSM improved the jejunal morphology and intestinal permeability in Langshan chickens. In conclusion, fermentation improved the feed value of the rapeseed meal mixture; replacing part of the soybean meal diet with fermented rapeseed meal mixture helped improve the slaughter performance and intestinal barrier of Langshan chickens.